Islamic Pedagogy and Digital Learning Tools: a Comparative Analysis of Traditional and Online Learning Environments - Amira Santos; Rafael De Oliveira; Fatima Ribeiro (World Journal of Islamic Learning and Teaching, 2024)
This article discusses the comparison between Islamic pedagogy in traditional and online learning environments, as well as the impact of digital learning tools on the teaching and learning process. By reviewing existing literature and conducting a comparative analysis, the study identifies the strengths and weaknesses of each method. Findings indicate that while online learning offers greater flexibility and accessibility, challenges such as social interaction and depth of learning remain concerns. The article concludes that the integration of Islamic pedagogy with digital learning tools can enrich the learning experience if applied wisely, emphasizing Islamic values in the digital context.